Whole-body vibration comfort measurement aboard the S. A. Agulhas II and just noticeable difference threshold testing in the laboratory - McMahon, Kim J. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.